Self-expanding vs. balloon-expandable transcatheter heart valves in small aortic annuli - Kornyeva, Anastasiya; Burri, Melchior; Lange, Rüdiger; Ruge, Hendrik (Frontiers in Cardiovascular Medicine, 2023)
Background Clinical consequences of prosthesis–patient mismatch (PPM) after transcatheter aortic valve replacement (TAVR) is currently in the focus of clinical research. Patients with small aortic annulus are at higher risk to display PPM. Data on incidence and clinical consequences of PPM after TAVR with either balloon-expandable (BEV) or self-expanding (SEV) transcatheter heart valves in small aortic annulus are sparse. Methods Patients with small aortic annulus (perimeter < 72 mm or aortic annulus area < 400 mm2) who underwent BEV or SEV with contemporary transcatheter heart valve types were identified from the institutional TAVR database. Propensity score matching was applied for imbalanced baseline characteristics between patients undergoing BEV or SEV. Echocardiography and clinical follow-up beyond 3 years was reported following VARC-3 recommendations. Primary endpoint was the incidence of pre-discharge PPM and its association with 3-year mortality. Results From a total of 507 patients with small aortic annulus, 192 matched patient pairs with SEV or BEV were identified. Mean age was 81 ± 7 (SEV) vs. 81 ± 6 (BEV) years (p = 0.5), aortic annulus perimeter was 69 ± 3 vs.69 ± 3 mm, (p = 0.8), annulus area was 357 ± 27 vs.357 ± 27 mm2 (p = 0.8), and EuroScore II was 5.8 ± 6.6 vs.5.7 ± 7.2 (p = 0.9). SEV resulted in less moderate (20% vs. 31%, p < 0.001) and severe pre-discharge PPM (9% vs.18%, p < 0.001) compared to BEV. At discharge (7 ± 4 vs. 12 ± 9 mmHg, p = 0.003) and at 1-year follow-up (7 ± 5 vs.13 ± 3 mmHg, p < 0.001), SEV displayed lower mean gradients compared to BEV. Estimated survival after SEV was 85% (95% confidence interval (CI): 80%–90%) at 1 year, 80% (95% CI: 75%–86%) at 2 years, and 71% (95% CI: 65%–78%) at 3 years; estimated survival after BEV was 87% (95% CI: 82%–92%) at 1 year, 81% (95% CI: 75%–86%) at 2 years, and 72% (95% CI: 66%–79%) at 3 years, with no significant difference among the groups (p = 0.9) Body surface area (OR: 1.35, p < 0.001), implantation of BEV (odds ratio (OR): 3.32, p < 0.001), and the absence of postdilatation (OR: 2.16, p < 0.001) were independent risk factors for any PPM. At 3 years, patients without PPM had a higher 3-year survival compared with patients with ≥moderate PPM (77% vs. 67%, p = 0.03). Conclusion BEV implantation in patients with small annulus was associated with a twofold higher incidence of pre-discharge severe PPM compared to SEV implantation. Survival at 3 years after TAVR was similar after BEV and SEV. However, patients with the absence of pre-discharge PPM had a higher 3-year survival compared to patients with ≥moderate PPM.